PATTERNS OF EMPOWERMENT OF SALIMAH DAKWAH INSTITUTIONS IN IMPROVING THE QUALITY OF WOMEN IN SELATPANJANG REGENCY OF MERANTI ISLANDS, RIAU PROVINCE - Ahmad Misbahul Anam; NIFTAHUL JANNAH (Jurnal Bina Ummat: Membina dan Membentengi Ummat, 2022)
Empowerment of women requires serious efforts, because of its strategic position in the natural life of Indonesia. Although the economic responsibility rests on the shoulders of men, family life always places women in almost the same position. Especially for underprivileged families or when women are left by their husbands. Women are forced to be the support of the family in various sectors. The Salimah Institute, which focuses on dealing with women, tries to provide empowerment assistance in the Selatpanjang area of ​​the Meranti Archipelago, Riau. The process is carried out through awareness, training and building opportunities for development.